Profit, Entry and Changes in Concentration: The Case of the Malaysian Food Manufacturing Sector (Malaysian Management Journal, 1997)
One of the major concerns of the body of economic analyses surrounding the theory of the firm is whether the profit behavior of oligopolistic industries differs from that of competitive industries. Theory suggest that where small groups of sellers accounts for a substantial proportion of an industry’s output, the recognition of mutual interdependence will result years significant progress has been made in developing a theoretical model to explain concentrating impact among consumer goods industries, and a number of empirical studies have been carried out to test the hypotheses which have been advanced. The findings however, are not conclusive. The work of Ekelund and Maurice (1969) has shown that concentration has no effect on profitability. Mann, Henning and Meehan (1967) on the other hand contended that the two are intimately connected. Similar findings were recorded in the work of Comanor and Wilson (1967) as well as that of Collins and Preston (1969).